Zastosowanie analizy skupień do klasyfikacji obiektów symbolicznych - Gliwa, Małgorzata (Approach divisive clustering Into symbolic objects classification, 2006)
The article presents divisive clustering method for symbolic data array. This is a hierarchical clustering method. Its main aim is division of the set of symbolic objects for K separate clusters, inside which objects are as homogeneous as possible, however each cluster is as different as possible. K. is the number of clusters given as input by the user. As a summary they present an example worked out by Sodas v. 1.2 programme.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 237-245